Reconstruction of energy dependence of the sensitivity of CdZnTe- and TlBr-detectors through the restricted data - Skrypnyk, A.I. (Вопросы атомной науки и техники, 2014)
Monte-Carlo method is used for investigating the energy dependence of sensitivity of CdZnTe- and TlBr-detectors of gamma-radiation, which operate in the mode of pulse-amplitude analysis. We researched the approximate formulae that describe this dependence in the range of gamma-quantum energies from 30 keV to 3 MeV. It is proposed a method for determining the tting parameters for approximate formulae through gamma-radiation spectra measured experimentally by several reference sources of gamma-radiation. In particular, it can be ²⁴¹Am, ¹³⁷Cs and ⁶⁰Co gamma-radiation sources. It is also discussed the measurements with additional radiation sources that can be used for improving an accuracy of reconstruction of energy dependence of detectors' sensitivity.